Accelerating matlab performance 1001 tips to speed up matlab programs - Altman, Yair (CRC Press Taylor & Francis Group, 2015)
The MATLAB® programming environment is often perceived as a platform suitable for prototyping and modeling but not for ""serious"" applications. One of the main complaints is that MATLAB is just too slow. Accelerating MATLAB Performance aims to correct this perception by describing multiple ways to greatly improve MATLAB program speed. Packed with thousands of helpful tips, it leaves no stone unturned, discussing every aspect of MATLAB. Ideal for novices and professionals alike, the book describes MATLAB performance in a scale and depth never before published